2018
DOI: 10.1093/toxsci/kfy243
|View full text |Cite
|
Sign up to set email alerts
|

Differential Toxicity of Alkylphenols in JEG-3 Human Placental Cells: Alteration of P450 Aromatase and Cell Lipid Composition

Abstract: Alkylphenols (APs) are a diverse class of chemicals that can cross the placental barrier and interfere with embryonic and fetal development. This work investigates the comparative toxicity, ability to inhibit aromatase activity, and to alter the lipid composition of 10 alkylphenols in the human placenta choriocarcinoma cell line JEG-3. Among the selected APs, 4dodecylphenol (DP), 4-heptylphenol (HP), and 4-cumylphenol (CP) showed the highest cytotoxicity (EC 50 : 18-65 mM). Aromatase inhibition was closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…21 This hypothesis is further supported by previous results observed in-vitro, where a general depletion of polyunsaturated lipids, namely PCs (36:5, 38:5, 38:6), PC-Ps and PEs/PE-Ps were detected both, in PLHC-1 and JEG-3 cells exposed to compounds that significantly induced the generation of ROS. 22 . However, other hypothesis like the reduced biosynthesis of highly unsaturated lipids in fish from polluted sites cannot be discarded.…”
Section: Methodsmentioning
confidence: 99%
“…21 This hypothesis is further supported by previous results observed in-vitro, where a general depletion of polyunsaturated lipids, namely PCs (36:5, 38:5, 38:6), PC-Ps and PEs/PE-Ps were detected both, in PLHC-1 and JEG-3 cells exposed to compounds that significantly induced the generation of ROS. 22 . However, other hypothesis like the reduced biosynthesis of highly unsaturated lipids in fish from polluted sites cannot be discarded.…”
Section: Methodsmentioning
confidence: 99%
“…These descriptor sets are obtained by removing the size descriptors (17)(18)(19)(20) from DS-A and DS-B, respectively. C * (4) pIGC 50 * ¼ 0:781EAv * þ 0:520eLUMO * þ0:435Sð1 orb Þ * À 0:220lS0 ! A * À 0:424IPv * À 0:318lS0 !…”
Section: Full Papermentioning
confidence: 99%
“…[3] They are being used as non-ionic surfactants, emulsifier, lubricant, or antioxidant in a variety of products such as laundry detergents, textiles, leather, paints, disinfecting cleaner, spot removers, hair colouring, cosmetic, adhesive, plastics, and pesticides. [4] It has been reported that APs are accumulated in lipids, bind to proteins, cause acute cytotoxicity and oxidative stress, cutaneous diseases such as vitiligo, and act as endocrine disrupters. [4] It has been reported that APs are accumulated in lipids, bind to proteins, cause acute cytotoxicity and oxidative stress, cutaneous diseases such as vitiligo, and act as endocrine disrupters.…”
Section: Introductionmentioning
confidence: 99%
“…Obesogenic properties have been associated with alkylphenols (derivatives of alkylphenol ethoxylates), which are nonionic surfactants that are used as cleaning agents [22]. There is also a body of evidence for the obesogenic effects of the pesticide dichlorodiphenyltrichloroethane (DDT) and its metabolite dichlorodiphenyldichloroethylene (DDE) [23].…”
Section: Sources and Classes Of Obesogensmentioning
confidence: 99%